Factores asociados al nivel de satisfacción de las usuarias del consultorio de consejería de planificación familiar en tres establecimientos de Salud I-3 Iquitos, 2023 - Del Aguila Jiménez, Juan Charles (2024)
Given the positive impact of family planning on reducing maternal, neonatal, and under-five mortality, as well as on reducing unintended pregnancies and abortions, it is essential to identify and address the factors that influence user satisfaction to promote greater continuity in the use of contraceptive methods and informed decisions in reproductive health. For this reason, this study aims to determine the factors associated with the level of satisfaction of users of the family planning counseling clinic in three healthcare facilities I-3 Iquitos, 2023. An observational and analytical study was conducted, with a sample of 126 patients. It was concluded that 81.6% of users are satisfied with the services. Lower satisfaction is recorded in waiting time (11.1%) and the information provided (47.6%). It was observed that there is no statistically significant association between the level of satisfaction in the studied dimensions and variables such as healthcare facility, age, origin, educational level, marital status, employment status, whether the user has children, and the reason for attending family planning (p>0.05). However, users from rural areas are less likely to be dissatisfied with waiting time (OR=0.14, p=0.013), and unmarried women are more likely to be dissatisfied with cleanliness (OR=5.0, p=0.049).